Pragmatic Analysis of The Somatism “Heart” In “Anna Karenina” - Gadoeva Mavlyuda Ibragimovna; Karimova Firangiz Ikhtiyerjonovna (Genius Journals, 2022)
This article is devoted to the pragmatic analysis of the somatism “heart” in “Anna Karenina” by Leo Tolstoy. This article reveals contextual meanings of the “heart” in different utterances. The findings are supported with the direct examples from the literary work
Keywords: pragmatics; pragmatical analysis; somatism; heart